2018
DOI: 10.4022/jafib.2012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Short and Long Term Recurrences of Paroxysmal AF after Radiofrequency Ablation. Is Blanking Period Really Benign?

Abstract: This was a prospective single centre study which included 36 consecutive patients who underwent radiofrequency catheter ablation (RFCA) of symptomatic paroxysmal AF at cardiology department in Ain shams university hospitals during the period from 2015 till 2017. Exclusion criteria included patients unwilling to give study consent and those with persistent AF, history of organized atrial tachycardia (AT) or atrial flutter (AFL), or previous history of AF ablation.Trans-oesophageal echocardiography was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These results are comparable with previously published data, regarding the phased-radiofrequency technique [6,7,8,9,10,21], including the recently published initial results from the multicenter GOLD AF registry [22], in which complete acute PV isolation was achieved in 93.8% of patients. Interestingly, the relapse in the blanking period was the strongest independent predictor ( p < 0.0001) of AF recurrence in long-term follow-up, which stands in line with earlier observations regarding both RF [23,24,25] and cryoablation [26] and supports the opinion that blanking-period relapses are possible signs of early PV reconnection.…”
Section: Discussionsupporting
confidence: 89%
“…These results are comparable with previously published data, regarding the phased-radiofrequency technique [6,7,8,9,10,21], including the recently published initial results from the multicenter GOLD AF registry [22], in which complete acute PV isolation was achieved in 93.8% of patients. Interestingly, the relapse in the blanking period was the strongest independent predictor ( p < 0.0001) of AF recurrence in long-term follow-up, which stands in line with earlier observations regarding both RF [23,24,25] and cryoablation [26] and supports the opinion that blanking-period relapses are possible signs of early PV reconnection.…”
Section: Discussionsupporting
confidence: 89%
“…The first 3 months after RFCA are known as a "benign or blanking period", with inflammatory changes and lesions of consolidations after RFCA, assumed as different causes of AFR. Recurrences are common and usually considered not relevant for long-term outcome: up to 50% of patients present AFR, and only half will develop later AFR [34]; on the other hand, absence of AFR predicts a successful outcome in the first year [37] and is associated with better long-term success rates [17,18].…”
Section: Comparison With Published Datamentioning
confidence: 99%
“…The intervention has favourable outcomes [12,13], but almost half of patients will have recurrences in the first year [1,8,14,15]. Early recurrences are frequently encountered [16], but do not always predict an unfavourable outcome [17][18][19]. After the first three months, atrial fibrillation recurrences (AFR) are associated with a higher recurrence risk in long-term monitoring [17,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, several studies have identified several major factors such as age, duration of AF, duration of AF paroxysm cycle, left and right atrium size (LA and RA), left ventricular ejection fraction (LVEF), as predictors of AF recurrence after the first successful RFA [6][7][8].…”
Section: Introductionmentioning
confidence: 99%